2001
DOI: 10.2307/2696111
|View full text |Cite
|
Sign up to set email alerts
|

Do "High-Performance" Work Practices Improve Establishment-Level Outcomes?

Abstract: Interest in the potential effects of different systems for organizing work and managing employees on the performance of organizations has a long history in the social sciences. The interest in economics, arguably more recent, reflects a general concern about the sources of competitiveness in organizations. A number of methodological problems have confronted previous attempts to examine the relationship between work practices and the performance of firms. Among the most intractable has been a concern about esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
281
2
12

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(306 citation statements)
references
References 22 publications
11
281
2
12
Order By: Relevance
“…Even if job satisfaction improves job performance, it may still reduce firm value net of costs. Cappelli and Neumark (2001) found that "high-performance" practices, which delegate responsibility to employees, increase labor costs. Thus, even though they also found weak evidence of improved productivity, there is no effect on overall labor efficiency (output per dollar cost).…”
Section: Difficulties In Identifying An Effectmentioning
confidence: 99%
“…Even if job satisfaction improves job performance, it may still reduce firm value net of costs. Cappelli and Neumark (2001) found that "high-performance" practices, which delegate responsibility to employees, increase labor costs. Thus, even though they also found weak evidence of improved productivity, there is no effect on overall labor efficiency (output per dollar cost).…”
Section: Difficulties In Identifying An Effectmentioning
confidence: 99%
“…5 Several studies on this issue nd that HPWOs increase productivity (see for example, Ichniowski et al 1997, Batt 1999, Appelbaum et al 2000. Empirical research on the wage e ects of HPWOs suggests that these systems also increase wages, indicating that the relationship between HPWOs and pro tability i s a m biguous (Appelbaum et al 2000, Capelli and Neumark 2001, Bauer and Bender 2002. Focusing solely on wages, however, this literature does not take into account other important components of total labor costs that might also be a ected by H P W Os.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the circumstances under which they are adopted make a difference (Kleiner et al, 2002). HRM practices that increase productivity typically increase worker compensation; thus, costs need not decline (Cappelli and Neumark, 2001). 14 Ichniowski et al (1997) also examine the effect of HRM practices on productivity.…”
mentioning
confidence: 99%